2023
DOI: 10.1093/jbcr/irad023
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Suicide by Self-immolation Among Children in Southern Iran

Abstract: Self-immolation is considered among the most rigorous acts of suicide. Lately, this act has increased in children. We evaluated the frequency of self-immolation among children in the largest burn referral center in southern Iran. This cross-sectional study was conducted from Jan 2014 to the end of 2018 at a tertiary referral burn and plastic surgery healthcare center in southern Iran. Subjects were pediatric self-immolation burn patients registered as outpatients or inpatients. The patients' parents were conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…When controlling for patient’s outcomes, there was no significant association between intentional injuries and mortality. Self-immolation is a devastating action and method of suicide with high fatality rates, and has been reported in our country 34 , 35 . Although univariant analysis reported suicide as a risk factor for unfavorable outcomes in our study cohort, the multivariable model showed no correlation between the two.…”
Section: Discussionmentioning
confidence: 90%
“…When controlling for patient’s outcomes, there was no significant association between intentional injuries and mortality. Self-immolation is a devastating action and method of suicide with high fatality rates, and has been reported in our country 34 , 35 . Although univariant analysis reported suicide as a risk factor for unfavorable outcomes in our study cohort, the multivariable model showed no correlation between the two.…”
Section: Discussionmentioning
confidence: 90%
“…Suicide kills thousands of people every year (Furqatovich & Sattorovich, 2022; Khademi et al, 2022; Pirkis et al, 2021). Self-immolation is a method of suicide where someone ends their life by setting themselves on fire (Cleary et al, 2021; Shahriarirad et al, 2023). Self-immolation is common in Africa, India, the Middle East, and Iran (El Hayek et al, 2022; Mohammadi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%